2018
DOI: 10.1093/jxb/ery035
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of lily HsfA3s in Arabidopsis confers increased thermotolerance and salt sensitivity via alterations in proline catabolism

Abstract: Overexpression of lily HsfA3s in Arabidopsis leads to changes in proline metabolism mediated via alterations in the regulation of specific bZIP transcription factors and confers increased thermotolerance and salt sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 74 publications
(100 reference statements)
1
44
0
1
Order By: Relevance
“…These data collectively suggest a role for CaHSL1 as a positive regulator in pepper basal and acquired thermotolerance under high humidity. Similarly, previous studies have found that some regulatory proteins in HSR signaling, for example, AtHsfA3, Aldehyde dehydrogenases (ALDH) (Zhao et al, 2017), ATPase6 (ALA6) (Niu et al, 2017) HsfA2 (Ogawa et al, 2007) in Arabidopsis and LlHsfA3A in lily ( Lilium longiflorum ) (Wu et al, 2018), FaHsfA2c in Festuca arundinacea (Wang et al, 2017) act as positive regulator in both basal and acquired thermotolerance, while LlHsfA3B (Wu et al, 2018) in lily acts as positive regulator only in acquired thermotolerance, salicylic acid dependent signaling (Clarke et al, 2004) promotes only basal thermotolerance, indicating that basal and acquired thermotolerance might be modulated by different signaling pathways with extensive crosstalks between them. Noticeably, our data showed that CaHSP24 and CaHSP24.2 that might localize to chloroplast (Heckathorn et al, 1996) were dramatically downregulated by silencing of CaHSL1 , coupled with significant decrease in Fv/Fm, whereas the transient overexpression of CaHSL1 significantly enhanced transcription of CaHSP24 and CaHSP24.2 as well as enhanced Fv/Fm, it can be speculated that as an indicator of plant thermotolerance, the stability of photochemical efficiency of PSII (Fv/Fm) might be contributed by multiple HSPs including CaHSP24 and CaHSP24.2 , as Fv/Fm differed in timing and amplitudes with CaHSP24 and CaHSP24.2 during response CaHSL1 silenced pepper plant to heat stress.…”
Section: Discussionsupporting
confidence: 52%
“…These data collectively suggest a role for CaHSL1 as a positive regulator in pepper basal and acquired thermotolerance under high humidity. Similarly, previous studies have found that some regulatory proteins in HSR signaling, for example, AtHsfA3, Aldehyde dehydrogenases (ALDH) (Zhao et al, 2017), ATPase6 (ALA6) (Niu et al, 2017) HsfA2 (Ogawa et al, 2007) in Arabidopsis and LlHsfA3A in lily ( Lilium longiflorum ) (Wu et al, 2018), FaHsfA2c in Festuca arundinacea (Wang et al, 2017) act as positive regulator in both basal and acquired thermotolerance, while LlHsfA3B (Wu et al, 2018) in lily acts as positive regulator only in acquired thermotolerance, salicylic acid dependent signaling (Clarke et al, 2004) promotes only basal thermotolerance, indicating that basal and acquired thermotolerance might be modulated by different signaling pathways with extensive crosstalks between them. Noticeably, our data showed that CaHSP24 and CaHSP24.2 that might localize to chloroplast (Heckathorn et al, 1996) were dramatically downregulated by silencing of CaHSL1 , coupled with significant decrease in Fv/Fm, whereas the transient overexpression of CaHSL1 significantly enhanced transcription of CaHSP24 and CaHSP24.2 as well as enhanced Fv/Fm, it can be speculated that as an indicator of plant thermotolerance, the stability of photochemical efficiency of PSII (Fv/Fm) might be contributed by multiple HSPs including CaHSP24 and CaHSP24.2 , as Fv/Fm differed in timing and amplitudes with CaHSP24 and CaHSP24.2 during response CaHSL1 silenced pepper plant to heat stress.…”
Section: Discussionsupporting
confidence: 52%
“…The activation of bZIP17 is controlled by HS in a manner similar to the regulatory mechanism that controls the UPR. In lily ( Lilium longiflorum ), promotion of thermotolerance by LlHSFAs involves regulation of bZip factors (AtbZIP11, AtbZIP44) [ 44 ]. In addition, the response pathway of bZIPs is activated during prolonged warming [ 19 ].…”
Section: Molecular Responses Of Plants Under Hsmentioning
confidence: 99%
“…Although the function of some HSFs in thermotolerance had been well characterized, their functions in other abiotic stresses remain largely unknown (Wu et al , 2018). Many aspects need to be determined, including: Do HSFs only bind to the HSE to regulate the gene expression?…”
Section: Introductionmentioning
confidence: 99%